A Booklet based on Islamic Parenting to Prevent Sexual Violence for Children and The Implications on Counseling - Karni, Asniti; Astarini, Dilla; Sa’adah, Diana Zumrotus (KONSELOR, 2023)
Every stakeholder needs to take action to prevent child sexual abuse because the number of cases of this type in children grows year, raising concerns among parents, families, schools, and communities about the future of their children. To stop sexual assault against children, we created an Islamic parenting guidebook. The goal of this project is to stop child sexual abuse by giving parents access to Islamic parenting guides and other material that will facilitate their Islamic upbringing and education. This will help them steer clear of undesirable things, like child sexual abuse. Parents whose children had been sexually abused were the study's subjects. Development research is the term for this kind of study. Using the ADDIE development models, researchers create booklets (Analysis, Design, Development, Implementation, evaluation). In order to gather data, three types of instruments are used: booklet validation tools, practical questionnaires, and effectiveness questionnaires. To ascertain the validity and applicability of employing percentage formulae, as well as the effectiveness of using formulas N Gain Score, data gathering procedures employ observation techniques, interviews, and documentation studies. Islamic parenting-based pamphlets are deserving of use since, according to the findings of the validation test conducted by linguists, designers, and material experts, the content is 95.17 percent valid. In terms of practicality, 92.4 percent fell into the category of somewhat practical. The Islamic parenting-based booklet can improve parents' awareness of education and parenting children to avoid sexual assault against children, as evidenced by the criteria's 64.4 percent effectiveness test, which indicates that it is effective.